2023
DOI: 10.1177/10760296231155177
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and 6-Month Mortality of Medical Oncology Patients With Incidental and Symptomatic Pulmonary Embolism: A Single-Institutional Retrospective Longitudinal Analysis

Abstract: This study aimed to identify clinical characteristics of cancer patients with incidental pulmonary embolism (IPE) and assess the variables associated with 30-day mortality in cancer patients with PE including symptomatic pulmonary embolism (SPE) and IPE. 6-Month mortality rate in cancer patients with SPE and IPE were also compared. We retrospectively analyzed electronic medical records of cancer patients with newly diagnosed PE between January 2016 and June 2021. We compared clinical and radiological character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…16 We have previously investigated the prevalence of incidental and SPE in patients with solid organ malignancies at our institution over a five year period and found that the overall incidence of PE was 3.12%, of which up to 51.9% of the PEs were noted incidentally for cancer staging or treatment evaluation or cancer recurrence detection. 17 During the course of the analysis of the data, it came to our attention that the patients with lung cancer listed as one of four cancer types which had significantly higher risk for PE compared to others and lung cancer patients account for the largest population that developed IPE which is consistent with previous study.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…16 We have previously investigated the prevalence of incidental and SPE in patients with solid organ malignancies at our institution over a five year period and found that the overall incidence of PE was 3.12%, of which up to 51.9% of the PEs were noted incidentally for cancer staging or treatment evaluation or cancer recurrence detection. 17 During the course of the analysis of the data, it came to our attention that the patients with lung cancer listed as one of four cancer types which had significantly higher risk for PE compared to others and lung cancer patients account for the largest population that developed IPE which is consistent with previous study.…”
Section: Introductionsupporting
confidence: 85%
“…A single-center, retrospective cohort study was conducted at the Ningbo First affiliated hospital of Ningbo University, a large metropolitan teaching hospital in southeast of China but different cancer with the earlier study. 17 All adult lung cancer patients (age ≥ 18 years) who developed incidental PE and symptomatic PE between January 2016 and June 2021 were eligible. Lung cancers were diagnosed by histologic or cytological examination and PE had to be objectively confirmed by standard radiological methods showing a high probability of PE.…”
Section: Patients and Designmentioning
confidence: 99%